How to detect the shortest period binary pulsars in the era of LISA. Issue 2 (7th December 2018) - Kyutoku, Koutarou; Nishino, Yuki; Seto, Naoki
ABSTRACT: We discuss a multimessenger strategy to detect radio pulses from Galactic binary neutron stars in a very tight orbit with the period shorter than 10 min. On one hand, all-sky surveys by radio instruments are inefficient for detecting faint pulsars in very tight binaries due partly to the rarity of targets and primarily to the need of correction for severe Doppler smearing. On the other hand, the Laser Interferometer Space Antenna ( LISA ) will detect these binaries with a very large signal-to-noise ratio and determine the orbital frequency, binary parameters, and sky location to high accuracy. The information provided by LISA will reduce the number of required pointings by two to six orders of magnitude and that of required trials for the corrections by about nine orders of magnitude, increasing the chance of discovering radio pulsars. For making full use of this strategy, it is desirable to operate high-sensitivity radio instruments such as Square Kilometre Array Phase 2 simultaneously with LISA .